Insurance Securitization - Hedging Catastrophe, Mortality and Longevity Risks - Rathi, Devesh (2010)
The insurance industry works on ‘The law of large numbers’ for calculating the premiums for each policyholder. The law aids in estimating the average expected total loss in writing multiple policies which are independent and exposed to the same loss potential. But the law breaks down in case of severe, low-probability events affecting multiple policies at the same time and may result in insolvency for the insurers, underestimating these losses. Catastrophic events like hurricanes, earthquakes, terrorist attacks; mortality events like pandemics and an unexpected increase in the average life expectancy of the human population due to medical advancement and drug discoveries are examples of such events which have a very low probability of occurrence but can have major economic consequences. ‘Reinsurance’, where these risks can be managed by further diversification both geographically and across multiple such events is the traditional mechanism for risk management in the insurance industry. But the reinsurance companies are also subjected to capacity constraints and may leave the insurers exposed to counterparty or credit risk when the potential losses and the correlations of the risks increase. Hence the insurance companies look at the capital markets to absorb these risks. The process of transferring the underwriting risks to capital markets is termed as ‘Insurance Securitization’ and the securities issued therein are termed as Insurance-Linked Securities (ILS). The ILS include Catastrophe (CAT) Bonds, Industry Loss Warranties (ILWs), CAT Swaps, Sidecars, Contingent capital (e.g. CatEputs), Mortality bonds, Longevity Bonds, Longevity Swaps, q-forwards and other futures and options, both OTC (over the counter) and exchange traded, which are used to hedge the catastrophe, mortality and longevity risks. ILS have low Betas since these risks have low correlations with financial markets and they enjoy higher yields than government issued securities, thus improving the risk-return tradeoffs of investor portfolios. This dissertation is a study of the ‘Insurance Securitization’ process and the use of ILS as a risk management tool for (re)insurance companies and as a diversification tool for investor portfolios. The report therefore provides a detailed overview of the ILS from both the hedging and investment perspectives, discussing their structure, the pricing mechanism used to value them and the recent developments in the markets for these securities. ILS are then compared based on their risks, transaction costs, flexibility and their market development to study their suitability and usability to various potential clientele. The report concludes with a discussion on the problems that have prevented ILS in achieving popularity levels comparable with equity and fixed income securities and potential solutions for the future success and widespread use of these securities.